2019
DOI: 10.1186/s12875-019-1055-z
|View full text |Cite
|
Sign up to set email alerts
|

Advanced practice nurses’ and general practitioners’ first experiences with introducing the advanced practice nurse role to Swiss primary care: a qualitative study

Abstract: BackgroundPrimary care is facing a multimorbid, ageing population and a lack of general practitioners (GPs), especially in rural areas. In many countries, advanced practice nurses (APNs) may be a potential solution for these challenges. Switzerland, however, is in the early stages of APN role development with a handful of pilot projects that are unresearched. Our aim was to explore the experiences of APNs and GPs involved in introducing the APN role to Swiss primary care.MethodsWe organised two focus group dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(110 citation statements)
references
References 24 publications
3
102
1
4
Order By: Relevance
“…Another reason could be that these patients were potentially underserved in this practice, and might have been speci cally assigned to her within the project. In a qualitative study by Gysin et al (14), most NPs who work in Swiss family practices reported a similar patient population they served. (24,25) 22)(14This goes in line with current political efforts to address the increase in chronic conditions.…”
Section: Interpretation and Comparison To Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Another reason could be that these patients were potentially underserved in this practice, and might have been speci cally assigned to her within the project. In a qualitative study by Gysin et al (14), most NPs who work in Swiss family practices reported a similar patient population they served. (24,25) 22)(14This goes in line with current political efforts to address the increase in chronic conditions.…”
Section: Interpretation and Comparison To Existing Literaturementioning
confidence: 99%
“…Since 2015, educational programs at master's level as well as postgraduate programs have focused more on clinical skills and competencies with the goal to better prepare the students for the NP role. Despite the political interest for new care models in lights of expected GPs shortages in rural areas, there are currently only a handful of ongoing NP pilot projects in primary care with the goal to address the health care needs of the increasing numbers of multimorbid elderly (13,14). One reason for the low number of projects might be that there is no legal framework which de nes the NPs' scope of practice, accountability or reimbursement options (12).…”
Section: Introductionmentioning
confidence: 99%
“…Data was collected from four different family practices in central and north-east Switzerland. These practices were selected because they all engaged an APN as part of a pilot project and were researched in larger evaluations (10,22). The projects varied in their implementation strategy.…”
Section: Settingmentioning
confidence: 99%
“…APNs tasks include the initial assessment of needs, routine follow-up care and advising patients on self-care management or life changes (3,8,9). In addition, several studies have shown that APNs, regardless of the eld of implementation (hospitals, general practice or hospital at home models) are likely to achieve higher patient satisfaction than GPs, due to longer consultations, the comprehensive provision of health information and advice, as well as their psychosocial (patient-centered) communication style (3,6,(10)(11)(12)(13). Furthermore, Jakimowicz (14) found in their review, that patients appreciated the involvement of APNs in their treatment because they displayed a focus on the patient as a person with additional concerns and not just on the disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation